HOUSEHOLDS’ PERCEPTION OF CLIMATE CHANGE EFFECTS IN RURAL ROMANIA - SURUGIU, Camelia; SURUGIU, Marius; MAZILESCU, Raluca; CRISTEA, Anca; MARGINEAN, Ileana (Annals of Spiru Haret University. Economic Series, 2018)
This paper is focused on the analysis of the impact of climate change on the households from rural Romania. Climate change may have an impact on different sectors of the economy, such as agriculture, food industry, energy sector, tourism, etc. Also, the impact is felt by households. In rural regions of Romania, the households are already facing various risks, related to lack of income, and also related to ageing population. This study aimed to underline how rural people relate to the climatic conditions with emphasis on the trend of major change in the various aspects of the weather, sources used to find information on climate change, reliability level of the climate change information provided by various sources, the possibility to adopt measures to tackle the effects of climate change, and so on. A number of 100 copies of the questionnaire were distributed among households in a rural area of Dâmbovița County, Romania - Petrești commune - in April, 2018, with the main purpose to test it. The respondents were selected randomly. Poor households are vulnerable to climate change because low income cannot provide a satisfactory degree of access to services needed in the protection against threats. Various adaptation strategies may be used by households confronted with negative effects of climate change.